Anti-thermal mobility in the Σ3 [111] 60° 11 8 5 grain boundary in nickel: Mechanism and computational considerations. (15th March 2017) - Humberson, Jonathan; Holm, Elizabeth A.
Abstract: Synthetic driving force molecular dynamics simulations were performed to examine anti-thermal mobility in the incoherent Σ3 [111] 60° 11 8 5 grain boundary in a model FCC metal. This boundary is faceted, and motion occurs by the movement of the 110 facets via the glide of sets of three Shockley partial dislocations. We explore several consequences of this motion mechanism, and show how additional factors must be taken into consideration when simulating this boundary. Graphical abstract: